Parvalbumin, calbindin, and calretinin immunostaining of 10 neural structures within the cerebellar cortex of 143 mammal species - Bhagwandin, Adhil; Sherwood, Chet C.; Hof, Patrick R.; Bertlesen, Mads. F.; Alagaili, Abdulaziz N.; Mohammed, Osama B.; Bennett, Nigel C.; Kaswera-Kyamakya, Consolate; Gilissen, Emmanuel; Manger, Paul R. (Frontiers in Mammal Science, 2024)
In the current study we employed immunohistochemical techniques to investigate the localisation of three calcium-binding proteins (parvalbumin, calbindin, and calretinin) in 10 neuronal structures of the cerebellar cortex (stellate cells, basket cells, parallel fibres, climbing fibres, Purkinje cells, granule cells, Golgi type II cells, Lugaro neurons, unipolar brush neurons, and mossy fibres) in 143 species from across the mammalian radiation. Most often, parvalbumin was localised in the neural structures of the molecular and Purkinje cell layers but was absent in the granule cell layer. Calbindin was most often immunolocalised in the neural structures of the Purkinje cell layer and mossy fibres, whereas calretinin was most often immunolocalised in the climbing fibres of the molecular layer and all neural structures of the granule cell layer. Despite this general consistency, variations in the localisation of these three calcium-binding proteins were found in every lineage, and almost every species, the one exception being the western tree hyrax that showed the full suite of most often observed calcium-binding protein chemoarchitecture for the mammalian cerebellar cortex. These consistencies and variances in the calcium-binding protein chemoarchitecture of the cerebellar cortex of mammals may play significant roles in the species-specific learning and refining of motor, perceptual, and cognitive skills and capacities required to survive in the environments they inhabit.